EFFECTIVENESS OF BOOKLETS AS EDUCATIONAL MEDIA TOINCREASE HYPERTENSION KNOWLEDGE: LITERATURE REVIEW - Mahardika Primadani; Isne Susanti; Eka Oktavia (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Hypertension is one of the chronic diseases with high prevalence that requires continuous educational efforts. Booklets as simple printed media are considered effective in increasing patient knowledge about the prevention and management of hypertension. This study is a literature review study that aims to analyze the effectiveness of using booklets as educational media in increasing knowledge of hypertension. Articles were obtained from the PubMed, Scopus, Web of Science, and Google Scholar databases using the keywords: "Booklet" OR "Educational Booklet" AND "Hypertension" OR "High Blood Pressure" AND "Knowledge" OR "Health Education". A total of 10 articles were selected based on the inclusion criteria and selected using the PRISMA diagram. The results of the review showed that the use of booklets consistently increased the knowledge of hypertension patients, both in adult, elderly, and adolescent groups. Booklets have also been shown to be effective when combined with mentoring from cadres or health workers. These results are in line with the theory of health literacy and educational communication which emphasizes the importance of visual media and readability. In conclusion, booklets are an effective educational media, and can be adapted for various target groups in an effort to increase knowledge about hypertension.